2001
DOI: 10.3758/bf03196184
|View full text |Cite
|
Sign up to set email alerts
|

Cued visual attention does not distinguish between occluded and occluding objects

Abstract: Does visual attention spread from the cued end of an occluded object to locations occupied by inferred portions of that object? We investigated this question by using a probe detection paradigm with two-dimensional (2-D) displays of occluded objects. Probes could appear in occluded or nonoccluded locations on either a cued or noncued object. Participants responded faster to probes appearing within the region of space occupied by the cued object. This was true not only when the probe appeared in positions separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Reliable object-based costs of ~9% were obtained for the lags from 130 to 520 msec. This pattern of results is consistent with that of previous studies, while additionally showing that object-based modulations survive occlusion not only in facilitatory (spatial) object cuing (Haimson & Behrmann, 2001;Moore & Fulton, 2005;Moore et al, 1998), but also in the inhibitory tagging of locations within an attended object in the AB paradigm.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Reliable object-based costs of ~9% were obtained for the lags from 130 to 520 msec. This pattern of results is consistent with that of previous studies, while additionally showing that object-based modulations survive occlusion not only in facilitatory (spatial) object cuing (Haimson & Behrmann, 2001;Moore & Fulton, 2005;Moore et al, 1998), but also in the inhibitory tagging of locations within an attended object in the AB paradigm.…”
Section: Discussionsupporting
confidence: 82%
“…One potential explanation for object-based costs could be that attentional effects (whether facilitatory or inhibitory) spread less effectively across luminance borders than within regions of the same brightness. On the other hand, however, object-based attention has been shown to operate on relatively complex object representations that require perceptual completion (e.g., Haimson & Behrmann, 2001;Moore & Fulton, 2005;Moore, Yantis, & Vaughan, 1998). In particular, these studies demonstrate that object-based attention can spread even across hidden portions of a partially occluded object (see Figure 4 for an example configuration), suggesting that attentional processes operate on completeobject representations.…”
Section: Methodsmentioning
confidence: 97%
“…Recently, Haimson and Behrmann (2001) claimed that visual attention does not distinguish between occluded and occluding objects. Their displays presented two pairs of crossed hockey sticks.…”
Section: Discussionmentioning
confidence: 99%
“…Using a two-rectangle paradigm, Egly et al (1994) were the first to show that facilitatory effects in selective attention induced by a cue appearing on an object can extend to uncued locations of the same object relative to an uncued object. Since then, several other studies have shown that the presence of objects in a visual display can influence the distribution of facilitatory cueing effects (e.g., Abrams & Law, 2000;Ariga, Yokosawa, & Ogawa, 2007;Avrahami, 1999;Brown & Denney, 2007;Chen, 1998;Chen & Cave, 2008;Goldsmith & Yeari, 2003;Haimson & Behrmann, 2001;Hecht & Vecera, 2007;Kravitz & Behrmann, 2008;Lamy & Egeth, 2002;Lamy & Tsal, 2000;Law & Abrams, 2002;Macquistan, 1997;Marino & Scholl, 2005;Marrara & Moore, 2003;Moore et al, 1998;Müller & Kleinschmidt, 2003;Pratt & Sekuler, 2001; Table 3 Summary of facilitatory cueing effects (in milliseconds) in studies using variants of the Egly et al two-rectangle task with different object contour salience Robertson & Kim, 1999;Shomstein & Behrmann, 2008;Shomstein & Yantis, 2004;Vecera, 1994). Real or illusory contours must be present to observe object-based facilitatory effects, and participants need to be aware of their presence (e.g., Ariga et al, 2007).…”
Section: Determinants Of Object-based Facilitatory Effectsmentioning
confidence: 99%
“…Nevertheless, the necessary-albeit not wholly sufficient-prerequisite for the observation of objectbased effects is the presence of physical or apparent contours (typically closed regions) in the visual display. Displays used to date have included outline and opaque rectangles and squares (e.g., Brown & Denney, 2007;Christ et al, 2002;Egly et al, 1994;Iani, Nicoletti, Rubichi, & Umiltà, 2001;List & Robertson, 2007;McAuliffe et al, 2001;Müller & von Mühlenen, 1996;Shomstein & Behrmann 2008;Theeuwes, Mathôt, & Kingstone, 2010;Vecera, 1994), hockey-stick-like figures (e.g., Haimson & Behrmann, 2001), overlapping objects (e.g., Behrmann, Zemel, & Mozer, 1998;Brawn & Snowden, 2000;Lavie & Driver, 1996;Law & Abrams, 2002;Moore et al, 1998), apparent rectangles and squares (e.g., Han, Wan, Wang, & Humphreys, 2005;Moore et al, 1998), thick lines (Robertson & Kim, 1999), open parallel lines (e.g., Avrahami, 1999;Marino & Scholl, 2005), outline ribbons (e.g., Avrahami, 1999), outline L-shapes (e.g., Leek, Reppa, & Tipper, 2003;Possin, Filoteo, Song, & Salmon, 2009;, groups of dots forming rectangles (e.g., Marrara & Moore, 2003), and outlines of 3-D objects (e.g., Bourke, Partridge, & Pollux, 2006;Gibson & Egeth, 1994). Some of the above object displays are shown in Tables 2, 3 and 4. If selection processes are mediated by representations of objects, the observation of object-based effects might reasonably be influenced by stimulus factors giving strong clues to object structure.…”
Section: Object-based Effects In Static Object Displaysmentioning
confidence: 99%